Matrilin-2 within a three-dimensional lysine-modified chitosan porous scaffold enhances Schwann cell migration and axonal outgrowth for peripheral nerve regeneration - Li, Neill Y.; Vorrius, Brandon; Ge, Jonathan; Qiao, Zhen; Zhu, Shuang; Katarincic, Julia; Chen, Qian (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Matrilin-2 is a key extracellular matrix protein involved in peripheral nerve regeneration. We sought to develop a biomimetic scaffold to enhance peripheral nerve regeneration through the incorporation of matrilin-2 within a chitosan-derived porous scaffold. We hypothesized that the use of such a novel biomaterial delivers microenvironmental cues to direct Schwann cell (SC) migration and improve axonal outgrowth during peripheral nerve regeneration. Materials and Methods: The effect of matrilin-2 on SC migration was evaluated with agarose drop migration assay in matrilin-2 coated dishes. SC adhesion was determined with SCs cultured atop tissue culture dishes coated with matrilin-2. Various formulations of chitosan vs. matrilin-2 in scaffold constructs were examined with scanning electron microscopy. The effect of the matrilin-2/chitosan scaffold on SC migration in the collagen conduits was determined by capillary migration assays. Neuronal adhesion and axonal outgrowth were evaluated with three-dimensional (3D) organotypic assay of dorsal root ganglions (DRG). DRG axonal outgrowth within the scaffolds was determined by immunofluorescence staining of neurofilaments. Results: Matrilin-2 induced SC migration and enhanced its adhesion. A formulation of 2% chitosan with matrilin-2 demonstrated an optimal 3D porous architecture for SC interaction. Matrilin-2/chitosan scaffold enabled SCs to migrate against gravity within conduits. Chemical modification of chitosan with lysine (K-chitosan) further improved DRG adhesion and axonal outgrowth than the matrilin-2/chitosan scaffold without lysine modification. Conclusions: We developed a matrilin-2/K-chitosan scaffold to mimic extracellular matrix cues and provide a porous matrix to enhance peripheral nerve regeneration. Taking advantage of matrilin-2’s capability to stimulate SC migration and adhesion, we formulated a porous matrilin-2/chitosan scaffold to support nerve outgrowth. Chemical modification of chitosan with lysine further improved matrilin-2 bioactivity in the 3D scaffold. The 3D porous matrilin-2/K-chitosan scaffolds have high potentials for enhancing nerve repair by stimulating SC migration, neuronal adhesion, and axonal outgrowth.